2021
DOI: 10.1590/1980-265x-tce-2020-0358
|View full text |Cite
|
Sign up to set email alerts
|

Structural Analysis of the Social Representations on Covid-19 Among Assistance Nurses

Abstract: Objective to analyze the structure of the social representations on Covid-19 among assistance nurses. Method a study with a qualitative approach, based on the Theory of Social Representations, with structural analysis, conducted with 178 nurses from Ceará, Brazil, from May to June 2020. The evocations were processed with the EVOC 2000® software, creating the four-house chart. IRAMUTEQ® was used to produce the similarity tree. Results the potential central nucleus was composed of “fear” and “isolation”, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
0
1
0
2
Order By: Relevance
“…One of the results of this study that drew the attention was the nurses' positive evaluation in relation to the performance in the care of suspected or confirmed COVID-19 patients. Previous studies have identified negative feelings among the nursing team, especially fear of being infected (7,10) . Thus, it can be considered that the participants' answers in this study evidence resilience and development of an emotional structure to face this moment of difficulty and adaptations in the work context.…”
Section: Discussionmentioning
confidence: 99%
“…One of the results of this study that drew the attention was the nurses' positive evaluation in relation to the performance in the care of suspected or confirmed COVID-19 patients. Previous studies have identified negative feelings among the nursing team, especially fear of being infected (7,10) . Thus, it can be considered that the participants' answers in this study evidence resilience and development of an emotional structure to face this moment of difficulty and adaptations in the work context.…”
Section: Discussionmentioning
confidence: 99%
“…(E010) Em estudo realizado sobre as representações sociais da Covid-19 para enfermeiros, identificou-se que o "medo" foi o elemento central da representação entre os profissionais de enfermagem. Segundo o autor, o medo pode estar associado ao risco de infecção dos trabalhadores ao coronavírus e o desenvolvimento da patologia, além do medo da morte 13 .…”
Section: Hoje a Minha Representação Frente A Essa Doença é Uma Repres...unclassified
“…A representação social da Covid-19 para os enfermeiros está em processo de construção, o isolamento social imposto pela pandemia dificultou a produção cientifica sobre a temática despertando insegurança na própria atuação profissional 13 . Diante do exposto é importante compreender que as RS da Covid-19 pode estar em processo de ancoragem no grupo de enfermeiros, pois observa-se que os participantes ainda estão em processo de busca e assimilação das informações sobre a doença e o vírus, bem como da construção de imagens, de simbolizações e de atitudes frente à doença.…”
Section: Mas Era Uma Doença Nova Era Um Inimigo Novo Que a Gente Não ...unclassified